The best damn sales book ever : - Greshes, Warren (Johw Wiley, 2006)
"Put this book on your must-read list if you want to learn successful strategies for taking your distribution team to the next level. Through motivation and education, Warren Greshes has captivated our very best top managers and producers. He pushes them to succeed and to keep their goals out in front of them, all the while maintaining a clear message, infused with his sense of humor. Warren has helped pave our way to success."